Rehabilitative landscape - Richardson, Lindsey J. (Kansas State University, 2009)
Druid City Hospital in Tuscaloosa, Alabama is one of the fastest growing heart, cancer, and rehabilitation hospitals in the southern United States. Although once characterized as one of the greatest modern innovations of the early century, the exterior is now outdated (DCH, 2009). However, as the hospital has increased in size and new additions constructed the identity and character of the once prized facility have been lost. Today the existing campus is a juxtaposition of mixed architecture styles and hastily planned construction efforts. The patients and employees of the Druid City Hospital believe that the exterior of the hospital fails to reflect the diligence and care being given within (DCH, 2009). The creation of a unified and cohesive exterior landscape would bring a strong connection between the interior and exterior and once again showcase the hospital as a marvel of it’s time. Through the implementation of spaces designed specifically for rehabilitation, the design of a cohesive landscape will address the current needs and existing conditions of the Druid City Hospital. The application of a health care garden typology and rehabilitative design elements adapted from Clare Cooper Marcus and Marni Barnes as well as the American Horticultural Therapy Association will aid in the design solutions and creation of acohesive and rehabilitative landscape for the Druid City Hospital.
Keywords: Landscape; Rehabilitation; health care design; typology; Druid City Hospital; Tuscaloosa; Landscape Architecture (0390)